2014
DOI: 10.1159/000365445
|View full text |Cite
|
Sign up to set email alerts
|

Western Dietary Pattern Interaction with APOC3 Polymorphism in the Risk of Metabolic Syndrome: Tehran Lipid and Glucose Study

Abstract: Background/Aims: Gene-dietary pattern interactions may contribute to the determination of a susceptibility to metabolic syndrome (MetS). The aim of this study was to evaluate the potential interactions of dietary patterns with the common genetic variant of APOC3 in relation to MetS in adults. Methods: In this individual matched nested case-control study, 755 MetS subjects and 755 controls were selected from among participants in the Tehran Lipid and Glucose Study. Dietary patterns were determined by factor ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…APOC3, in the same family with APOA4, inhibits triglyceride hydrolysis. The common genetic variant of APOC3 contributes to metabolic syndrome in adults[ 17 ]. APOC3 plays an important role in regulating the metabolism of triglyceride-rich lipoproteins and has been regarded as a main component of chylomicrons and very-low-density lipoprotein (VLDL).…”
Section: Discussionmentioning
confidence: 99%
“…APOC3, in the same family with APOA4, inhibits triglyceride hydrolysis. The common genetic variant of APOC3 contributes to metabolic syndrome in adults[ 17 ]. APOC3 plays an important role in regulating the metabolism of triglyceride-rich lipoproteins and has been regarded as a main component of chylomicrons and very-low-density lipoprotein (VLDL).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, SNPs in the vitamin D receptor ( VDR ) gene, which affect vitamin D availability [20,21], have been associated with osteoporosis predisposition in postmenopausal women with low calcium intakes [22]. Moreover, SNPs in genes encoding lipid proteins such as apolipoprotein C3 ( APOC3 ) and apolipoprotein A1 ( APOA1 ) conferred a higher risk of metabolic syndrome in subjects with a Western dietary pattern [23,24]. Likewise, a genetic variant in the cytochrome P450 family 1 subfamily A member 2 ( CYP1A2 ) gene was associated with an increased risk of hypertension and CVD in moderate and heavy coffee drinkers [25,26].…”
Section: Genetic Background and Nutritional Prescriptionsmentioning
confidence: 99%
“…Unlike studies focused on the effect of single food item and nutrient, examination of dietary patterns, which assess the effects of overall diet and determined by factor analysis can be proxy indicators of real food consumption and availability, providing a more realistic representation of everyday eating habits 7 . Several studies have demonstrated that dietary pattern is an important factor associated with MS 8 9 10 11 12 13 . There are three cross-sectional studies explored the association between dietary pattern and prevalence of MS in Chinese 14 15 16 .…”
mentioning
confidence: 99%